2021
DOI: 10.1089/apc.2020.0233
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Mobile Health Strategy to Improve Linkage to and Engagement with HIV Care for People Living with HIV, Tuberculosis, and Substance Use in Irkutsk, Siberia

Abstract: In Irkutsk, Siberia, there is a high prevalence of HIV and tuberculosis (TB) coinfection. Mobile health (mHealth) strategies have shown promise for increasing linkage to and engagement in care for people living with HIV (PLWH) in other contexts. We evaluated outcomes for a cohort of PLWH, TB, and substance use in Irkutsk after participation in a multi-feature mHealth intervention called MOCT. Sixty patients were enrolled during hospitalization for TB. We evaluated participant app usage, linkage to HIV care pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The cohort and additional usage details are described elsewhere. 28 Patients’ perceptions of the platform’s usability and acceptability were assessed following 6 months of participation in the intervention ( table 2 ). The survey was completed by 47 participants (seven patients were lost to follow-up, two were deceased by six months, one did not attend the 6-month assessment and three attended the assessment but did not complete the survey).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cohort and additional usage details are described elsewhere. 28 Patients’ perceptions of the platform’s usability and acceptability were assessed following 6 months of participation in the intervention ( table 2 ). The survey was completed by 47 participants (seven patients were lost to follow-up, two were deceased by six months, one did not attend the 6-month assessment and three attended the assessment but did not complete the survey).…”
Section: Resultsmentioning
confidence: 99%
“…Pilot study participants demonstrated improved rates of linkage to care at the AIDS Centre and ongoing engagement with the platform by six months as well as better rates of medication refill and a lower propensity towards developing the composite outcome of death and failure to achieve viral suppression at six months. 28 Following contextual evaluation of patient and provider perceptions and platform testing and modification, the programme has been implemented across the Irkutsk oblast (a federal region similar to a state or province). Enrolment has expanded to four TB Referral Hospital filial (affiliated) clinics following hospital administrative approval and engagement of clinic leadership.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations